The Economic Crisis Affects the Cohesion Policy and Slows Down the Migration in Europe - Petronela Daniela Feraru (CES Working Papers, 2014)
The economic crisis has made it difficult to achieve the key objectives of the European Union and the cohesion policy as a result of the increase in regional disparities. The main causes are the decrease of employment rates, increasing poverty and social exclusion. Among the effects of the crisis, there have been identified within the present work, on the one hand, some Member States of the European Union, who are facing more problems, but also fewer public resources and, on the other hand, the trend of population migration slowdown in regions marked by large flows of migrant workers in the pre-crisis period. All these issues highlight the need to reconsider the cohesion policy. In the present work, we are trying to establish to what extent the tools for the reduction of discrepancies between EU Member States on the management and impact can be successfully developed within the new cohesion policy for 2014-2020, starting from the compromises made for the purpose of connecting the European objectives to the national ones.
Keywords: A13; E24; F22; F43; J61; 330; cohesion; migration; economic crisis; sustainable development Romania